Photocatalytic performance of hybrid WO3/TiO2 nanomaterials for the degradation of methylene blue under visible light irradiation. Issue 10 (9th August 2021) - Tahir, Muhammad Bilal; Farman, Sohail; Rafique, Muhammad; Shakil, Muhammad; Khan, Muhammad Isa; Ijaz, Mohsin; Mubeen, Iqra; Ashraf, Maria; Nadeem Riaz, Khalid
ABSTRACT: In this work, the hybrid WO3 /titanium dioxide (TiO2 ) photocatalysts were prepared using hydrothermal method for the degradation of methylene blue dye under visible light irradiation. The scanning electron microscope, Fourier transform infrared spectroscopy, ultra violet visible absorption and photoluminescence emission spectroscopy were employed to study the morphology, structure and functional groups, elemental composition and purity, and optical properties. The morphological results showed the rectangular structure of pure WO3 with size of 36–550 nm, whereas spherical structures were also observed after incorporation of TiO2 in WO3 . The monoclinic phase was found with high crystallinity. The composite sample (2% TiO2 /WO3 ) showed seven times improved photocatalytic activity as compared to pure samples. The improvement may attribute to the increase of the photo-absorption effect by the TiO2, the cooperative effect of the WO3, optimal band gap and unique morphological structures. Considering our present study as cost-effective method, the as-synthesised photocatalysts can be suitable and give a new perspective for applied use in energy and environmental applications.